Zonulin transgenic mice show altered gut permeability and increased morbidity/mortality in the DSS colitis model - Sturgeon, Craig; Lan, Jinggang; Fasano, Alessio (Annals of the New York Academy of Sciences, 2017)
Increased small intestinal permeability (IP) has been proposed to be an integral element, along with genetic makeup and environmental triggers, in the pathogenies of chronic inflammatory diseases (CIDs). We identified zonulin as a master regular of intercellular tight junctions linked to the development of several CIDs. We aim to study the role of zonulin‐mediated IP in the pathogenesis of CIDs. Zonulin transgenic Hp2 mice (Ztm) were subjected to dextran sodium sulfate (DSS) treatment for 7 days, followed by 4–7 days' recovery and compared to C57Bl/6 (wild‐type (WT)) mice. IP was measured in vivo and ex vivo, and weight, histology, and survival were monitored. To mechanistically link zonulin‐dependent impairment of small intestinal barrier function with clinical outcome, Ztm were treated with the zonulin inhibitor AT1001 added to drinking water in addition to DSS. We observed increased morbidity (more pronounced weight loss and colitis) and mortality (40–70% compared with 0% in WT) at 11 days post‐DSS treatment in Ztm compared with WT mice. Both in vivo and ex vivo measurements showed an increased IP at baseline in Ztm compared to WT mice, which was exacerbated by DSS treatment and was associated with upregulation of zonulin gene expression (fourfold in the duodenum, sixfold in the jejunum). Treatment with AT1001 prevented the DSS‐induced increased IP both in vivo and ex vivo without changing zonulin gene expression and completely reverted morbidity and mortality in Ztm. Our data show that zonulin‐dependent small intestinal barrier impairment is an early step leading to the break of tolerance with subsequent development of CIDs.